IHI ID 07 Decreasing emergency department length of stay for admitted pediatric patients. (December 2018) - Carter, Lindsay; Solemina, Kristen; Mascola, Jessica; Peer, Michael; Greenspan, Peter
Abstract : Background: Prolonged emergency department (ED) length of stay (LOS) can lead to safety risks including handovers, medication and meal delays, high patient to nursing ratios, and lack of accommodations for families, potentially negatively affecting patient care and satisfaction. In 2016, 75% of admitted pediatric patients at MassGeneral Hospital for Children spent >2 hours waiting for a bed. Objectives: To decrease ED median LOS of admitted pediatric patients by 8% in 12 months. Methods: Four working groups targeted the process and developed interventions. Primary outcome measure was ED LOS. Process measures included provider and nursing handoffs within 30 min of an available inpatient bed and percentage of inpatient pre-noon discharges. Balance measures included safety report filings regarding ED transfers and readmissions within 48 hours of discharge. Baseline median and variability was determined through statistical process control charts using healthcare rules of interpretation for improvement analysis. Results: There were 12 months of baseline and 16 months of intervention involving 4846 patients. Median LOS decreased by 10.1%, from 5.73 hours to 5.15 hours. MD and RN handoffs within 30 min of bed availability improved by 11.4% and 17.9%, respectively. There was no statistically significant change in percentage of pre-noon discharges. There was no increase in safety reports or readmissions. Conclusions: Through a multimodal intervention process involving education, process measures, and engaged leadership, there was a significant improvement in ED LOS for admitted pediatric patients without increases in readmissions or safety issues. Initiatives are ongoing to address barriers to timely inpatient discharges and sustaining the intervention over time.